Power-to-liquids-based high conversion fischer-tropsch synthesis over supported ruthenium catalysts - Chaza, Nyika Mufudzi (Department of Chemical Engineering, 2026)
Limited research has been conducted on Ru as the main active metal in a FTS catalyst, therefore, three investigations were conducted in this research project to determine the best combination of parameters for synthesising a suitable Ru-based PtL-FTS catalyst (i.e., a catalyst that achieves >90% CO conversion, >85% C5+ hydrocarbon selectivity, as well as <5% and <1% CH4 and CO2 selectivities, respectively): Effect of different (1) catalyst synthesis methods (i.e., incipient wetness impregnation (IWI) vs. slurry impregnation (SI)), (2) pre-treatment methods (i.e., drying vs. drying+calcination vs. drying+calcination+washing), and (3) support materials (i.e., alumina (Al2O3) vs. silica-modified-alumina (SiOx-m-Al2O3) vs. silica gel (SiO2)) on FTS performance. In the first investigation, Al2O3-supported Ru catalysts (with 20 wt.-% Ru) were prepared via IWI and SI using ruthenium(III) chloride hydrate (RuCl3.xH2O) as a metal precursor. The pre-treatment conditions explored in the second investigation were as follows: Al2O3-supported Ru catalysts prepared via SI were either (a) dried at 120 °C for 10 h, (b) dried at 120 °C for 10 h and calcined at 400 °C for 2 h under stagnant air at atmospheric pressure, or (c) dried at 120 °C for 10 h, calcined at 400 °C for 2 h, and washed using 25 wt.-% aqueous ammonia (NH3) to remove residual chloride (Cl-) ions. Finally, the third investigation on the effect of support materials on FTS performance involved three 20 wt.-% Ru-loaded Al2O3-, SiOx-m-Al2O3-, and SiO2-supported catalysts. All three catalysts were synthesised and pre-treated in the same way, i.e., prepared via SI, dried at 120 °C, and calcined under stagnant air at 400 °C. Catalyst activation (via reduction in pure H2 at 425 ºC for 16 h) and FTS performance evaluation (at 220 ºC, 17.5 bar, and 7200 mL/gcat/h using a synthesis gas mixture of 60:30:10 H2:CO:He) were conducted on a four-reactor testing unit connected to an on-line GC-TCD instrument for permanent gas analysis. Hydrocarbon (C1-100) product sampling was conducted throughout each FTS experiment via ampoules and wax collection for off-line GC-FID analysis. The effect of catalyst synthesis methods (SI vs. IWI) on FTS performance was investigated using two catalysts, viz., 20 Ru/Al2O3 calcined (SI) and 20 Ru/Al2O3 calcined (IWI). The 20 Ru/Al2O3 calcined (SI) catalyst showed better FTS performance, with maximum-to-minimum CO conversions of 91-to-80% when compared with the 20 Ru/Al2O3 calcined (IWI) catalyst with CO conversions of 90-to-59%. Both catalysts exhibited deactivation as a function of time-on-stream (TOS), however, the 20 Ru/Al2O3 calcined (IWI) catalyst showed a greater total CO conversion loss of 31%. Product selectivities remained constant despite the catalyst deactivation as a function of TOS over both catalysts, with <5% CH4 selectivities, <1% CO2 selectivities, and >84% C5+ selectivities being achieved. Moreover, the deactivation in both catalysts was mainly attributed to carbon deposition (confirmed via TEM, Raman spectroscopy, and TGA). It is hypothesised that the less graphitic carbon (detected on the 20 Ru/Al2O3 calcined (IWI) catalyst) is responsible for the higher extent of deactivation through the blockage of surface active sites for CO hydrogenation. However, catalyst deactivation via v carbon deposition had no effect on the product formation mechanisms of the FTS as all product selectivities (CH4, CO2, and C5+) for both catalysts remained constant over 168 h TOS. The effect of catalyst pre-treatment methods on FTS performance was investigated using three catalysts, viz., 20 Ru/Al2O3 dried (SI), 20 Ru/Al2O3 calcined (SI), and 20 Ru/Al2O3 calcined+washed (SI). The 20 Ru/Al2O3 calcined (SI) catalyst displayed the best FTS performance, with >80% CO conversions when compared with the 20 Ru/Al2O3 dried (SI) and 20 Ru/Al2O3 calcined+washed (SI) catalysts that reached final CO conversions of 49% and 60%, respectively. All three catalysts underwent deactivation, however, the 20 Ru/Al2O3 calcined+washed (SI) catalyst showed the largest extent of deactivation, with a maximum-to-minimum CO conversion loss of 85-to-59% when compared to 68-to-49% and 91-to-80% for the 20 Ru/Al2O3 dried (SI) and 20 Ru/Al2O3 calcined (SI) catalysts, respectively. It was noted that the product selectivities were constant despite the catalyst deactivation as a function of TOS, with <8% CH4 selectivities, <1% CO2 selectivities, as well as >85% C5+ selectivities being realised. The deactivation in all three catalysts was attributed to carbon deposition, however, deactivation in the 20 Ru/Al2O3 calcined+washed (SI) catalyst was postulated to also be an effect of NHx species that may have been pre-adsorbed onto the catalyst. On the hand, the 20 Ru/Al2O3 dried (SI) catalyst exhibited the lowest CO conversions throughout the 168 h TOS when compared with the 20 Ru/Al2O3 calcined (SI) and 20 Ru/Al2O3 calcined+washed (SI) catalysts. This result was attributed to the structure sensitivity of the Ru nanoparticles i.e., smaller Ru particles (ca. 5.3 nm) in the 20 Ru/Al2O3 dried (SI) catalyst are less active when compared to the Ru particles (>9.4 nm) in 20 Ru/Al2O3 calcined (SI) and 20 Ru/Al2O3 calcined+washed (SI) catalysts. The effect of support materials (Al2O3 vs. SiOx-m-Al2O3 vs. SiO2) on FTS performance was investigated using three catalysts, viz., 20 Ru/Al2O3 calcined (SI), 20 Ru/SiOx-m-Al2O3 calcined (SI), and 20 Ru/SiO2 calcined (SI). The 20 Ru/SiOx-m-Al2O3 calcined (SI) catalyst exhibited the best FTS performance during the TOS, with maximum-to-minimum CO conversions of 93-to-87% when compared with the 20 Ru/Al2O3 calcined (SI) and 20 Ru/SiO2 calcined (SI) catalysts that reached CO conversions of 91-to-80% and <35%, respectively. The 20 Ru/SiO2 calcined (SI) catalyst attained the lowest CO conversions of <35%, highest CH4 (up to 14%) and CO2 (up to 4%) selectivities, and formed no C2+ hydrocarbons throughout the 168 h TOS, which was attributed to the possible early deposition of carbon and consequent blockage of surface active sites for CO hydrogenation. On the other hand, the 20 Ru/SiOx-m-Al2O3 calcined (SI) and 20 Ru/Al2O3 calcined (SI) catalysts exhibited similar product selectivities of <3% CH4, <1% CO2, and >85% C5+. Moreover, the SiO2 support had a higher amount of strong acid sites than the Al2O3-containing supports, which may have exacerbated the carbon deposition. It was postulated that the SiOx modification of the Al2O3 support was responsible for the limited carbon deposition and low extent of deactivation observed for the 20 Ru/SiOx-m-Al2O3 calcined (SI) catalyst during the FTS. Therefore, the 20 Ru/SiOx-m-Al2O3 calcined (SI) catalyst was regarded as the most suitable PtL-FTS catalyst from this research project.